2019
DOI: 10.1371/journal.ppat.1007633
|View full text |Cite
|
Sign up to set email alerts
|

Central memory CD8+ T cells become CD69+ tissue-residents during viral skin infection independent of CD62L-mediated lymph node surveillance

Abstract: Memory CD8+ T cells in the circulation rapidly infiltrate non-lymphoid tissues following infection and provide protective immunity in an antigen-specific manner. However, the subsequent fate of memory CD8+ T cells after entering non-lymphoid tissues such as the skin during a secondary infection is largely unknown. Furthermore, because expression of CD62L is often used to identify the central memory (TCM) CD8+ T cell subset, uncoupling the physical requirement for CD62L-mediated lymph node homing versus other f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 54 publications
8
42
0
Order By: Relevance
“…Memory CD8 + T cells are antigen-experienced cells that show an improved response to second challenge, in comparison to naive cells. The relation of central memory CD8 + T cells and effector CD8 + T cells detected in the skin during inflammation has been established in CHS model as well as in viral infection (Gaide et al, 2015, Mbitikon-Kobo et al, 2009, Osborn et al, 2019. Our data demonstrate that expression of Gal-1 controls the generation of central memory CD8 + T cells, and the secretion of IFNγ, which account for the exacerbated skin inflammation.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 56%
“…Memory CD8 + T cells are antigen-experienced cells that show an improved response to second challenge, in comparison to naive cells. The relation of central memory CD8 + T cells and effector CD8 + T cells detected in the skin during inflammation has been established in CHS model as well as in viral infection (Gaide et al, 2015, Mbitikon-Kobo et al, 2009, Osborn et al, 2019. Our data demonstrate that expression of Gal-1 controls the generation of central memory CD8 + T cells, and the secretion of IFNγ, which account for the exacerbated skin inflammation.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 56%
“…Data from other models show that T RM cells display variable phenotypes during infection with different pathogens. One report showed that T CM cells trafficked to the skin during vaccinia virus infection and converted to CD69 + T RM cells, without CD103 expression (48). Lymphoid T RM cells displayed a similar phenotype during recovery from LCMV infection (19).…”
Section: Discussionmentioning
confidence: 99%
“…22 Moreover, central memory CD8 T cells can also traffic into tissues and can become tissue resident cells and provide improved tissue METFORMIN ON HIV-SPECIFIC T CELL TO PD-L1 BLOCKADE surveillance in shock and kill HIV remission strategies. 23 Our observations of increased central memory population CD8 T cells may have a beneficial effect on improving HIV-specific CD8 T cell responses.…”
Section: Discussionmentioning
confidence: 75%